Respuesta :
Answer:
h(0) is equal to 2.
Step-by-step explanation:
In order to find this, we first put 0 in for x in the g(x) equation.
g(x) = 2x - 1
g(0) = 2(0) - 1
g(0) = -1
Now that we have this, we can stick the answer for g(x) into the f(x) equation.
f(x) = 1 - g(x)
f(x) = 1 - -1
f(x) = 1 + 1
f(x) = 2
The value of [tex]h(0)[/tex] is 2.
It is given that,
- [tex]g(x)=2x-1[/tex]
- [tex]h(x)=1-g(x)[/tex]
Explanation:
We have,
[tex]h(x)=1-g(x)[/tex]
[tex]h(x)=1-(2x-1)[/tex]
[tex]h(x)=1-2x+1[/tex]
[tex]h(x)=2-2x[/tex]
Substitute [tex]x=0[/tex] in the above function.
[tex]h(0)=2-2(0)[/tex]
[tex]h(0)=2-0[/tex]
[tex]h(0)=2[/tex]
Thus, the value of [tex]h(0)[/tex] is 2.
Learn more:
https://brainly.com/question/19358860